2015
DOI: 10.1007/s11858-015-0712-5
|View full text |Cite
|
Sign up to set email alerts
|

Flow-chart proofs with open problems as scaffolds for learning about geometrical proofs

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…In the first learning phase, constructing flow-chart proofs in an open problem situation helped to scaffold students' understanding of the structure of deductive proofs (Miyazaki, Fujita, & Jones, 2015). Since students at this early stage of learning about a deductive proof might see it as a rather meaningless set of symbols about the properties of geometric shapes, through the follow-chart proving we provided a visualisation of the structure of the proofs.…”
Section: A Sequence Of Lessons To Introduce the Structure Of Deductivmentioning
confidence: 99%
“…In the first learning phase, constructing flow-chart proofs in an open problem situation helped to scaffold students' understanding of the structure of deductive proofs (Miyazaki, Fujita, & Jones, 2015). Since students at this early stage of learning about a deductive proof might see it as a rather meaningless set of symbols about the properties of geometric shapes, through the follow-chart proving we provided a visualisation of the structure of the proofs.…”
Section: A Sequence Of Lessons To Introduce the Structure Of Deductivmentioning
confidence: 99%
“…The conclusion of the study by [10] also showed that the use of Flow Proof can overcome students' difficulties in performing proof. Similarly to research by [11], the use of Flow Proof with open problems encouraged student's development toward understanding the structure of proof by providing assumptions with conclusions.…”
Section: Fig 4 Students Learning Resultsmentioning
confidence: 99%
“…Hasil penelitian menunjukkan bahwa ketika siswa diberikan suatu masalah dalam Geometri dan siswa diminta untuk menuliskan premis serta pernyataan yang akan dibuktikan, begitu juga dengan membangun diagram Flow Proof dan Two-Column Proof, terlihat bahwa siswa dapat menyelesaikan pembuktian, 2) penelitian Miya zaki, Fujita, Jones, dan Iwanaga (2017). Hasil penelitian menunjukkan bahwa penggunaan Flow Proof pada pelajaran Geometry dapat mengatasi kesulitan siswa dalam melakukan pembuktian, dan 3) penelitian Miyazaki, Fujita, dan Jones (2015). Hasil penelitian menunjukkan bahwa penggunaan Flow Proof dengan problem terbuka mendorong perkembangan siswa terhadap pemahaman struktur bukti dengan memberikan berbagai hubungan asumsi dengan kesimpulannya.…”
Section: Pendahuluanunclassified